Content and Quality Analysis of Websites as a Patient Resource for Temporomandibular Disorders - Burçin Akan (Galenos Yayinevi, 2020)
Objective:The purpose of this study was to evaluate the content and quality of internet information resources in Turkey about temporomandibular disorders (TMDs).Methods:In July 2020, the keywords "jaw joint disease" (çene eklemi rahatsızlığı) and "jaw joint pain" (çene eklemi ağrısı) were searched on Google, Bing, YAHOO!, and Yandex. The first 20 websites were listed for 2 keywords on the 4 search engines. Scientific articles, product websites, repetitive sites, advertisements, and irrelevant websites were excluded from the list. The remaining 77 websites were assessed using the Quality Criteria for Consumer Health Information (DISCERN), Global Quality Score (GQS) and Journal of American Medical Association (JAMA) benchmarks. The topics related to TMDs that were thought to be important in informing the patient were determined and the Temporomandibular Disorder Content Score (TMDCS) was calculated to evaluate whether these contents were available on the website.Results:The sources of the 77 websites included dentists in private practice (6.5%, n=5), hospitals/polyclinics (32.5%, n=25), universities (6.5%, n=5), and others (54.5%, n=42). The total DISCERN scores of all websites included were poor (average score 26.96). Mean scores of JAMA, GQS, and TMDCS were 1.75, 2.31, and 8.4, respectively.Conclusion:The quality and reliability of the information on the websites related to TMDs are poor. Clinicians should be aware that patients may have access to unreliable or incomplete information. There is a need for improvement on websites about TMDs, especially by professionals through imparting more comprehensive and reliable information.